Effect of capacity building on production of safe and profitable leafy vegetables among farmers in Ibadan City of Nigeria - Olajide-Taiwo, L. O.; Cofie, Olufunke O.; Odeleye, O.M.O.; Olajide-Taiwo, F. B.; Olufunmi, Y.; Adebayo, O.S.; Alabi, O.O. (2011)
Eighty percent of the fresh leafy vegetables consumed by about three million people who live in Ibadan city of Nigeria and its environ are produced within and around the city by farmers in backyards, vacant land, near streams, road sides, barracks and government offices. Due to lack of adequate training among other factors, farmers make sub-optimal profit margins and produce vegetables which are dangerous to human health due to misuse of agrochemicals. This study was embarked upon for a period of three months, to build the capacity of vegetable farmers on how to produce safe and profitable vegetables using good agricultural practices (GAP) and improved production packages with minimal use of appropriate agro-chemicals. Two groups of 60 women vegetable farmers in Odogbo army barrack of the city were involved. Farmers' production practices and associated problems were documented through Focus Group Discussion (FGD). Innovative capacity building strategies building on farmers' resources and on-farm demonstration (OFAD) in the form of urban producers' field school (UPFS) focusing on the three most important vegetables - Corchorus, Celosia and Amaranthus - to the farmers was set up to address the problems. Weekly trainings were conducted and farmers were encouraged to apply the knowledge gained on their private farms. Thirty farmers each from participating and non-articipating farmers were randomly selected to compare their yield, quality of harvest and economic returns after the training. Data were analyzed using t-test. There was significant difference (p<0.05) between the yield obtained by participating and non-articipating farmers.Economic gains of the participating farmers also increased by 300% on the average due to improved quality of produce and higher market price. There should be conscious effort to assist vegetable farmers through capacity building in order to ensure supply of good quality vegetables and increase economic gains in the city.